Dairy farming systems' adaptation to climate change - Silva, Emiliana (2017)
The measure of climate change in dairy farms can be achieved by using the emissions of methane by the ruminants converted in CO2 equivalent (CO2-eq). In order to know the impact of future quotes of methane in the Azorean dairy milk farms, a decision model is built to the Azorean intensive grazing system of dairy farms. Some scenarios of methane levels reductions from 10 to 75% are considered and their impact is evaluated upon dairy farms income, level of CO2-eq emissions and intensity level of grazing system. The results have shown that any reduction of the methane level always implies a consequent decrease in income. If the CO2-eq has to be limited than there is the need to find alternative income activities for farmers in order to preserve economic sustainability.